Fibromuscular dysplasia in argentina. a registry from the secondary hypertension working group of the argentine society of hypertension (sahara-df). project protocol and preliminary results - Aparicio, Lucas Sebastián; Alfie, José; Barochiner, Jessica; Bluro, Ignacio; Bresso, Paula; Castellaro, Carlos; Cianfagna, Daniela; Conti, Paula; Cuffaro, Paula Edit; Díaz, María Alicia; Ghezzi, Lidia; Márquez, Diego; et al. (Revista del Hospital Italiano de Buenos Aires, 2019)
In Argentina there are no epidemiological data regarding fibromuscular dysplasia. Building a National Registry may provide information leading to updated consensus and recommendations for a correct diagnosis, assessment and treatment. Data gathering for the Argentine Registry of Fibromuscular Dysplasia (SAHARA-DF) was initiated in October 2015. By 2019, 49 patients were confirmed (44 women, 38 hypertensives, age 45.3 ± 17.2 years, 12 with a neurological presentation). Twenty-two patients had multi-site vascular lesions, in spite of a diagnosis bias due to lack of supporting studies in almost half of the cases. The renovascular site was the most affected, followed by the carotid and iliac sites, and multifocal lesions were more frequent than unifocal (35 versus 14, respectively). Associated aneurysms were found in 13 cases, and arterial dissection in 4. Twenty-two renal angioplasties were performed, 14 with stent placement. In this preliminary study of an Argentinian population, the systemic nature of the disease is evidenced, and a call for action arises regarding the need for discussing the diagnostic algorithm and treatment method.
Keywords: fibromuscular dysplasia; secondary hypertension; blood pressure; carotid dissection; intracranial aneurysm